The Small Quantum System (SQS) Instrument at European XFEL: Results of commissioning and first experiments. Issue 11 (January 2020) - Meyer, M; Baumann, T M; Achner, A; Boll, R; De Fanis, A; Grychtol, P; Ilchen, M; Mazza, T; Montaño, J; Music, V; Ovcharenko, Y; Rennhack, N; et al.
Synopsis: The Small Quantum System (SQS) instrument on the soft X-ray undulator SASE3 of the European XFEL went into operation during 2018. We present first results from the instrument characterizing the focus properties and the time-of-flight as well as velocity map imaging spectrometers of the AQS chamber.